Association between serum uric acid and phase angle in patients with type 2 diabetes mellitus: A cross-sectional study - Hu, Yezi; Liu, Jie; Jin, Hui (Frontiers in Endocrinology, 2023)
Background: The purpose of this analysis was to investigate the associations between serum uric acid and phase angle in patients with type 2 diabetes mellitus. Methods: In this retrospective cross-sectional study, we included 200 type 2 diabetes mellitus (T2DM) patients treated during 2018 to 2019 in Zhongda Hospital Southeast University. Phase angle (PhA) and other body composition indicators were measured by bioelectrical impedance analysis(BIA). All patients underwent routine clinical examinations at the day of hospitalization, and the basic information and clinical symptoms of these patients were recorded. Results: Serum uric acid was significantly associated with PhA(p < 0.001). Overall, in the crude model and minor, all adjusted models (Crude model、Model I-II), the phase angle increased as the tertiles of serum uric acid increased. In the minor adjusted model (ModelⅠ,adjustment for age ,duration) fully adjusted model (Model Ⅱ, adjustment for age ,duration Lpa, , BMI,WHR), the adjusted β for participants in tertiles of serum uric acid were 0.26 (95% CI: 0.05-0.46) and 0.32 (95% CI: 0.11-0.54) respectively, compared with those in lowest tertile 1. Conclusions: There was a nonlinear relationship between serum uric acid and PhA in T2DM patients and phase angle increases as uric acid increases within a certain range, and this effect disappears when uric acid exceeds a certain value.